2016
DOI: 10.1039/c6ce00676k
|View full text |Cite
|
Sign up to set email alerts
|

Imine-tautomers of aminothiazole derivatives: intriguing aspects of chemical reactivities

Abstract: Intriguing reactivities of positional isomers 1-(5-methylthiazol-2-yl)-3-(4-nitrophenyl)thiourea (L 1 ) and 1-(4-methylthiazol-2-yl)-3-(4-nitrophenyl)thiourea (L 2 ) towards environment polluting ions such as mercuric, fluoride, bromide and solvents provide scope to study various self-assemblies formed under different conditions and allied applications. The solid state structures of L 1 and L 2 revealed that both adopt the imine form. However, the number of symmetry independent molecules in asymmetric units as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 95 publications
0
8
0
Order By: Relevance
“…6,7 Certain anion-guiding chemical reactions of thiourea derivatives such as hydrolysis and bromination are useful in anion detection. 8 With the aid of a syn or anti conformer of a thiourea derivative, distinction of acetate and fluoride ions is possible. 9 On the other hand, conformations play an important role in self-assemblies of urea 1012 and thiourea 1315 derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Certain anion-guiding chemical reactions of thiourea derivatives such as hydrolysis and bromination are useful in anion detection. 8 With the aid of a syn or anti conformer of a thiourea derivative, distinction of acetate and fluoride ions is possible. 9 On the other hand, conformations play an important role in self-assemblies of urea 1012 and thiourea 1315 derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…Among possible isomers, which can be formed through Pathways 1 and 2 ( Scheme 2 ) both due to the N-1/N-3-oxide equilibrium and/or prototropic tautomerism in the molecule [ 25 , 26 , 27 , 28 ], the most stable one is 3aC ; however, the energy difference between models with different locations of hydrogen (at amine/thiazole N: 3aA / 3aC and 3aB / 3aD ) is less than 1 kcal/mole, suggesting the possible coexistence of both structures ( Table 1 ). The preferable location of the benzofuroxan oxygen moiety is at the N1 atom that is almost by 4 kcal/mol more advantageous compared to the tautomers with an oxygen atom located at N3.…”
Section: Resultsmentioning
confidence: 99%
“…On the example of the simplest representative of benzofuroxan and aminothiazole hybrids with R=R 2 =R 3 =H 3a, three possible ways have been considered for aromatic nucleophilic substitution reaction: Pathway 1-attack of electrophile on the exocyclic NH 2 , Pathway 2-attack of an electrophile on the endocyclic nitrogen atom and Pathway 3-attack on the carbon atom in Position 5 (Scheme 1). Among possible isomers, which can be formed through Pathways 1 and 2 (Scheme 2) both due to the N-1/N-3-oxide equilibrium and/or prototropic tautomerism in the molecule [25][26][27][28], the most stable one is 3aC; however, the energy difference between models with different locations of hydrogen (at amine/thiazole N: 3aA/3aC and 3aB/3aD) is less than 1 kcal/mole, suggesting the possible coexistence of both structures (Table 1). The preferable location of the benzofuroxan oxygen moiety is at the N1 atom that is almost by 4 kcal/mol more advantageous compared to the tautomers with an oxygen atom located at N3.…”
Section: Quantum Chemical Calculationsmentioning
confidence: 99%
“…Both HL 1 and HL 2 can have two forms amide and imino‐ketone (Scheme 1) due to amine‐imine tautomerism. [ 17 ] The X‐ray structures revealed that both molecules exist in the imino‐ketone form (Figure 1). The shorter C(8)N(1) bond length compared with the C(8)N(2) bond length indicates the double bond character of the former (Table 2).…”
Section: Resultsmentioning
confidence: 99%